Efficacy analysis of percutaneous balloon compression therapy for trigeminal neuralgia guided by three-dimensional digital subtraction angiography navigation - Xu, Zhennan; Li, Hui; Liu, Mingfa; Xu, Ke (Frontiers in Neurology, 2025)
IntroductionThe aim of this study was to evaluate the clinical efficacy of percutaneous microballoon compression guided by three-dimensional digital subtraction angiography (DSA) navigation in treating primary trigeminal neuralgia.MethodsWe retrospectively analyzed 40 patients with primary trigeminal neuralgia who underwent percutaneous microballoon compression under three-dimensional digital subtraction angiography navigation between January 2019 and April 2025. Post-operative pain relief was assessed 1 d, 1 month, and 3 months post-surgery.ResultsAll 40 patients underwent three-dimensional digital subtraction angiography dual-volume imaging and 3D-Dyna-computed tomography cranial reconstruction at the pre-puncture, needle placement, balloon positioning, and balloon inflation stages. We adjusted the balloon morphology during inflation, considering cranial reconstruction and balloon positioning, for optimization. Post-operatively, all patients showed significant pain relief: 38 achieved immediate pain resolution, one resolved at 3 days, and one at 2 weeks. Overall, all 40 patients developed facial numbness, two developed perioral herpes, one developed diplopia, and one experienced transient masseter muscle weakness; all these resolved with treatment. Two patients showed recurrence during follow-up.DiscussionThree-dimensional digital subtraction angiography navigation-guided percutaneous microballoon compression is a safe and minimally invasive technique for the treatment of trigeminal neuralgia. Real-time 3D-Dyna-computed tomography reconstruction enables the visualization of the balloon-petrous apex relationship, enhancing procedural precision and therapeutic outcomes.